EFEKTIVITAS EKSTRAK BABADOTAN (AGERATUM CONYZOIDES L.) TERHADAP TINGKAT KEMATIAN LARVA SPODOPTERA LITURA F. - Lumowa, Sonja Verra Vinneke (EUGENIA, 2011)
ABSTRACT   Effectivity of babadotan extract (Ageratum conyzoides L.) to mortality larval of Spodoptera litura F. had been conducted at the Laboratory of Wood Chemistry, Faculty of Forestry and the Laboratory of Biology Education, Faculty of Teacher Training and Education University of Samarinda Mulawarman from June to  October 2010. The study aimed to determine the effectivity of the babadotan extract to mortality of larval S. litura (instarIV). Research activities were the preliminary test and advanced test. Preliminary test was  the concentration of six treatments namely 0%, 0.001%, 0.01%, 0.1%, 1% and 10%, while the advanced test consisted of four treatments viz the concentration of 0%, 5%, 10% and 20%. The result showed that the concentration of 10% resulted death rate by 60% of test larvae in preliminary trials. Whereas, the treatment of advanced test with a concentration of 20% revealed that the death rate was 100% with the periode of mortality 26-60 minutes. Keywords: extract babadotan, Spodoptera litura larvae